ANALISIS LITERASI DIGITAL DALAM PEMBELAJARAN PADA SISWA KELAS III SD MUHAMMADIYAH 8 MALANG - Innany Mukhlishina; Murtyas Galuh Danawati (Universitas PGRI Adi Buana Surabaya, 2023)
The development of technology-based education is growing rapidly so that it affects the world of education. Based on the results of a preliminary study at SD Muhammadiyah 8 Malang, they have used digital tools in learning. The purpose of this study is to describe the implementation of digital literacy in learning in third grade students of SD Muhammadiyah 8 Malang. This type of research is descriptive qualitative research. Data collection techniques used observation, interviews, field notes, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, data verification, and checking the validity of the data. The results showed that the implementation of digital literacy consisted of time management, cyber bullying management, cyber security management, privacy, critical thinking, and digital empathy.